Role as a mechanism for rotating leadership in a group - Sheard, A. G.; Kakabadse, Andrew P.; Kakabadse, Nada K. (Emerald Group Publishing Limited, 2009)
Purpose - This study seeks to propose that executives need to be prepared to adopt roles as a mechanism for rotating leadership if those groups of which they are a part are to perform to their full potential. Design/methodology/approach - A validated framework provides insight into the leadership roles executives can adopt when part of formal, informal and temporary groups. The methodology adopted is qualitative, focusing on the application of previously developed frameworks. Findings - Adopting a role is found to enable the rotation of leadership within a group, which in turn facilitates development of the group. Research limitations/implications - A one-organisation intensive case study of a multinational engineering company engaged in the design, development and manufacture of rotating turbomachinery provides the platform for the research. The frameworks will require validating in organisations of different demographic profiles. Practical implications - The concepts advanced and implications discussed provide an insight into the role-based nature of leadership. The practical steps individual executives can take to adopt a role, and in so doing develop the group of which they are a part, are highlighted. Originality/value - This paper is an investigation into, and study of, the process by which executives adopt roles as a mechanism for rotating leadership within a group. In so doing, it is suggested that executives contribute more positively to the development of the groups of which they are a part by being more adaptive and responsive to changes in their surrounding context.